Genetic heredity study of aluminum toxicity tolerance in rice based on the means and variances analysis - de Paula Ferreira, Reinaldo; Sigueyuki Sediyama, Carlos; Cruz, Cosme Damião; Silva Freire, Marlene (Pesquisa Agropecuaria Brasileira, 1997)
An Al toxicity tolerant rice cultivar, Guaporé, was crossed with a sensitive, IAC 899, to study the genetic heredity of Al tolerance in rice. The root length character was evaluated for parents and for the generations as well as the F1 and F2, and backcrosses for both parents, after 10 days growing in 20 ppm Al nutritive solution. The results showed that tolerance to Al toxicity in rice performed as a quantitative character. The means of F1s, F2s, RC1s and RC2s were similar to the tolerant parent, showing the dominance of the high tolerance to toxicity caused by Al. The most important genetic effects to determine root length were the means and the additive effect. The epistatic interactions additive x additive, additive x dominant and dominant x dominant explain 16.83% of the observed means for the generations utilized. However, with the logarithmic transformation the epistasis effect was reduced to 13.28%, allowing the use of the additive-dominant genetic model to explain the variation observed on the character studied.